Immunoprophylactic and immunotherapeutic control of hormone receptor-positive breast cancer - Aitziber Buqué (Nature Portfolio, 2020)
Current preclinical models to investigate human HR + breast cancer progression and response to immunotherapy in vivo are limited. Here, the authors demonstrate that mammary tumours driven by a synthetic progestin combined with an oral carcinogen recapitulate several immunobiological features of human HR + breast cancers.